A simulation study on capacitor switching: article / Noorasmah Mohd Ali - Mohd Ali, Noorasmah (2010)
The subject of power quality has achieved substantial consideration in recent years. From the largest industrial consumer to the smallest commercial facility, power quality affect the day to day of almost every process in operation today. Transient is the most common power quality disturbances encountered today. Transient in distribution network can damage key equipment in which potentially having a great impact on the system reliability. These transient may occur during the switching operation. Capacitor bank switching (CBS) is the example of switching operation that is used for power factor improvement, elimination of voltage drop on long feeder and control of reactive power. When a capacitor bank energized, the transient occur are not typically harmful to utility equipment but the highest transient voltage occur when the uncharged capacitor is switched at the voltage peak. This project focus on simulating the capacitor switching and methods to reduced the transient impact in distribution network.